Rhododendron anthropogon ssp. hyphenanthum plants growing at the Tromsø Arctic-Alpine Botanical Garden - Campbell, Sandy (2024)
This dwarf rhododendron was blooming at the Tromsø Arctic-Alpine Botanical Garden (latitude 69.6769° N). This plant is from the Himalayas